How a Systems Perspective Improves Knowledge Acquisition and Performance in Analytical Procedures - Brewster, Billy E. (The Accounting Review, 2011)
ABSTRACT: Auditors are required to understand dynamic business environments as part of the performance of analytical procedures. Prior evidence, though, suggests that auditors have difficulty understanding such environments. This study reports an experimental investigation of techniques that help auditors to identify incorrect management representations by developing expectations that are both accurate and adaptive to changing business conditions. My predictions suggest that analyzing a dynamic client environment through a systems perspective enhances information-processing ability, which then improves both evidence discrimination and the assimilation of new audit evidence. Results reveal that participants taking a holistic systems-based view of a client environment develop more coherently organized mental models that increase their likelihood of identifying management representations that are inconsistent with industry evidence. Furthermore, these participants more efficiently use their information-processing ability, thereby improving assimilation of newly learned evidence to understand how changing business conditions affect their initial expectations.